Age and composition of Antarctic sub-glacial bedrock reflected by detrital zircons, erratics, and recycled microfossils in the Ellsworth Land-Antarctic Peninsula-Weddell Sea-Dronning Maud Land sector (240 degrees E-0 degrees-015 degrees E) - Veevers, J. J.; Saeed, Ayesha (Gondwana Research, 2013)
The age and composition of the 14 x 10(6) km(2) of Antarctica's surface obscured by ice is unknown except for some dated detrital minerals and erratics. In remedy, we present four new analyses (U-Pb age, T-DM(C), epsilon Hf, and rock type) of detrital zircons from Neogene turbidites as proxies of Antarctic bedrock, and review published proxies: detrital hornblendes analysed for Ar-Ar age and bulk Sm-Nd isotopes: Pb isotope compositions of detrital K-feldspars: erratics and dropstones that reflect age and composition: and recycled microfossils that reflect age and facies. This work deals with the 240 degrees E-0 degrees-015 degrees E sector, and complements Veevers and Saeed's (2011) analysis of the 70 degrees E-240 degrees E sector. Each sample is located in its ice-drainage basin for backtracking to the potential provenance. Gaps in age between sample and upslope exposure are specifically attributable to the provenance. The major provenance of detritus west of the Antarctic Peninsula (AP) is West Antarctica, and of detritus east of the AP East Antarctica. We confirm that the Central Antarctic provenance about a core of the Gamburtsev Subglacial Mountains (GSM) and the Vostok Subglacial Highlands (VSH) contains a basement that includes igneous (mafic granitoids) and metamorphic rocks with peak U-Pb ages of 0.65-0.50, 1.20-0.9, 2.1-1.9, 2.8-2.6, and 3.35-3.30 Ga, T-DM(C) of 3.6-1.3 Ga, and mainly negative epsilon Hf. The potential provenance of zircons of 650-500 Ma age with T-DM(C) ages of 1.55 Ga, and of zircons of 1200-900 Ma age with positive epsilon Hf lies beneath the ice in East Antarctica south and southeast of Dronning Maud Land within the Antarctic part of the East African-Antarctic Orogen. Zircons with the additional ages of 1.7-1.4 Ga, 2.1-1.9 Ga, and 3.35-3.00 Ga have a potential provenance in the GSM. (c) 2012 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.